Adjusting health care: practicing care for socially vulnerable type 2 diabetes patients - Sofie á Rogvi; Ann Dorrit Guassora; Gitte Wind; Nina Tvistholm; Solveig May-Britt Jansen; Inge Birgitte Hansen; Hans Joergen Duckert Perrild; Ulla Christensen (BMC, 2021)
Abstract Background Type 2 diabetes cluster in lower social groups and people with type 2 diabetes from lower social groups experience more complications, benefit less from health services and live shorter lives than people with type 2 diabetes from higher social groups. Different logics govern diabetes care and potentially influence the possibility of socially vulnerable type 2 diabetes patients to access and benefit from health services. In order to understand which practice and underlying logic enable socially vulnerable type 2 diabetes patients to access and benefit from diabetes care we aim to describe what professionals at a specialized diabetes clinic do to adjust services to patient's needs and make the tasks involved in diabetes care doable for socially vulnerable patients and how this work is embedded in an organizational and moral context. Methods Ethnographic fieldwork combining participant observation and interviews was carried out between February 2017 and March 2018 in a specialized diabetes clinic located in a socially deprived area in the capital region of Denmark. Sixteen patients (9 male, 7 female, aged 35-73 years) and 12 professionals (7 doctors, 4 nurses, 1 secretary) participated in the study. We used Annemarie Mol's concept of "the logic of care" to guide our analysis. Results Our analysis shows that the logic of care and the care practices in this clinic are characterized by a needs-based approach to treatment involving adjustment of services (permeability, timing, and content) and seeing the patient as a person with many needs. Throughout our description of selected care practices, we both characterize how health professionals practice this particular logic of care and the organizational and normative conditions that this logic is entangled with. Conclusions Practicing diabetes care based on patients' needs involves individualization, something often described as an element of patient centred care. Our study shows that this ideal of individualization and adjustment of treatment is possible in practice. Organizational flexibility and an organizational culture that values patient needs enable needs-based care. In order for socially vulnerable type 2 diabetes patients to benefit from health services it is necessary to create conditions under which professionals can attend to these patients' multiple and complex needs. Adjusting care to these needs demand a variety of professional efforts some of which are hardly predictable or standardisable.